Penerapan Aljabar Max-Plus pada Permasalahan Penjadwalan Angkutan Perdesaan di Jombang - Nahlia Rakhmawati; Ririn Febriyanti (Jurnal Matematika MANTIK, 2017)
The existence of ideal public transportation is still a dream of many cities in Indonesia, including the city of Jombang. The high consumption of Jombang people to motor vehicles, causing traffic jams in the school area. In this research, a directed graph from 3 rural transit routes to get the design of scheduling model using max-plus algebra. From the analysis results to the model obtained the period of departure of rural transport is 10 minutes once, with two initial departure time interval. Arranged departure schedules allow rural transport always at every meeting point during school hours.